2022
DOI: 10.3390/jof8090922
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Onychomycosis in Diabetic Patients: A Case-Control Study Performed at University Hospital Policlinico in Catania

Abstract: Diabetes is characterized by an increased rate of serum glucose due to defects in insulin secretion, insulin action or both conditions. Glucose excesses can lead to extended cellular damage, with the consequence of several infectious and non-infectious skin disorders. The aim of the present study was to evaluate the toenail onychomycosis incidence in diabetic patients and healthy ones. The non-interventional, retrospective study was performed at the mycology laboratory of the University hospital “Policlinico-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Sufficient data were available to compare the prevalence of NDM onychomycosis in clinically suspected patients who underwent single ( n = 81,515) or repeat sampling ( n = 32,171) 16,50–112 . Across both Global North and Global South regions, results from studies where single sampling is performed showed a higher degree of variability compared to studies that utilized the recommended repeat sampling approach (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient data were available to compare the prevalence of NDM onychomycosis in clinically suspected patients who underwent single ( n = 81,515) or repeat sampling ( n = 32,171) 16,50–112 . Across both Global North and Global South regions, results from studies where single sampling is performed showed a higher degree of variability compared to studies that utilized the recommended repeat sampling approach (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in our study, patients with diabetes had increased risk of onychomycosis development similar to previous literature. For example, in a 2016 Italian retrospective study including 668 non-diabetic and 47 diabetic patients, 55.3% (N = 26) of diabetic patients and 25.2% (N = 169) of non-diabetic patients were diagnosed with onychomycosis (P < 0.0001) [ 39 ]. In a 2008–2009 Japanese cross-sectional observational study of 71 patients, an unadjusted multiple logistic regression model found that not washing feet every-day was associated with a significantly increased risk of onychomycosis among diabetic patients (OR: 3.45, 95% CI: 1.24–9.65; P = 0.018), though data was not significant in the age and sex adjusted model (OR: 2.37; 95% CI: 0.76–7.33; P = 0.136) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin reactions caused by insulin therapy: lipohypertrophy (most common manifestation, at the site of insulin injection), lipoatrophy, erythema, local infections, subcutaneous nodules, allergies [ 24 ]. Lipohypertrophy is the most common local reaction after insulin injection, affecting approximately 27% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The drugs frequently incriminated belong to the sulphonylurea class (glibenclamide, tolbutamide, chlorpropamide), which, according to some authors, also induce psoriatic or lichenoid eruptions. The occurrence of pemphigus vulgaris has also been reported very rarely [ 4 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation